Trend of oral and pharyngeal cancer mortality in Brazil in the period of 2002 to 2013 - Perea, Lillia Magali Estrada; Peres, Marco Aurélio; Boing, Antonio Fernando; Antunes, José Leopoldo Ferreira (Revista de Saúde Pública, 2018)
OBJECTIVE: To analyze the trend of oral and pharyngeal cancer mortality rates in the period of 2002 to 2013 in Brazil according to sex, anatomical site, and macroregion of the country. METHODS: The mortality data were obtained from the Mortality Information System and the population data were obtained from the Brazilian Institute of Geography and Statistics. The trend of the rates standardized by sex and age was calculated using the Prais-Winsten estimation, and we obtained the annual percentage change and the respective 95% confidence intervals, analyzed according to sex, macroregion, and anatomical site. RESULTS: The average coefficient of oral cancer mortality was 1.87 per 100,000 inhabitants and it remained stable during the study period. The coefficient of pharyngeal cancer mortality was 2.04 per 100,000 inhabitants and it presented an annual percentage change of -2.6%. Approximately eight in every 10 deaths occurred among men. There was an increase in the rates of oral cancer in the Northeast region (annual percentage change of 6.9%) and a decrease in the Southeast region (annual percentage change of -2.9%). Pharyngeal cancer mortality decreased in the Southeast and South regions with annual percentage change of -4.8% and -5.1% respectively. Cancer mortality for tonsil, other major salivary glands, hypopharynx, and other and unspecified parts of mouth and pharynx showed a decreasing trend while the other sites presented stability. CONCLUSIONS: Pharyngeal cancer mortality decreased in the period of 2002 to 2013. Oral cancer increased only in the Northeast region. Mortality for tonsil cancer, other major salivary glands, hypopharynx, and other and ill-defined sites in the lip, oral cavity, and pharynx decreased.